2018
DOI: 10.1177/0956462418803983
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and efficacy of partner notification for curable sexually transmitted infections in sub-Saharan Africa: A systematic review

Abstract: Comprehensive case management of sexually transmitted infections (STIs) includes partner notification. We reviewed the recent literature evaluating the acceptability and efficacy of partner notification strategies (i.e. direct patient referral, provider referral, or expedited partner treatment) for curable STIs in sub-Saharan Africa. We conducted a systematic search following PRISMA guidelines: published January 2008 to June 2017 in the English language, study in sub-Saharan Africa, and discussion of any curab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…9 Of those who successfully notified their partner, 25% (range 0-77%) had partners that sought treatment. 9 In another study at a community-based clinic in South Africa, participants reported notifying only 64% of partners of their STI diagnosis. 10 Among South Africans, fears of intimate partner violence and relationship dissolution have been identified as barriers to partner notification following diagnosis with a STI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Of those who successfully notified their partner, 25% (range 0-77%) had partners that sought treatment. 9 In another study at a community-based clinic in South Africa, participants reported notifying only 64% of partners of their STI diagnosis. 10 Among South Africans, fears of intimate partner violence and relationship dissolution have been identified as barriers to partner notification following diagnosis with a STI.…”
Section: Introductionmentioning
confidence: 99%
“…5,8 However, in a recent systematic review of studies conducted in sub-Saharan Africa, the proportion of index STI patients who notified their partner using this strategy was only 53% (range 23-95%). 9 Of those who successfully notified their partner, 25% (range 0-77%) had partners that sought treatment. 9 In another study at a community-based clinic in South Africa, participants reported notifying only 64% of partners of their STI diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In CT intervention programs and guidelines in several countries, including the United Kingdom [7], Canada [8], the Netherlands [9], and Germany [9], partner notification (PN) is an essential individual and public health strategy to avoid re-infection of a treated index patient and reduce the burden of infections [10,11]. To expand the active screening of CT, a program in China called Shenzhen Gonorrhea and Chlamydia intervention pilot (SGCIP) was launched by the Health and Family Planning Commission of Shenzhen Municipality in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of PN varies in different studies: 53% successful direct patient referral in sub-Saharan Africa [11], 73% successful PN in Sweden [18], 76.4% successful PN in the United States [19], and 51% successful PN by patient referral card in Peru [20]. Also, improving the efficacy of PN was found to be more cost-effective than increasing the coverage of CT screening [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation